2013
DOI: 10.1038/ni.2782
|View full text |Cite
|
Sign up to set email alerts
|

Two waves of distinct hematopoietic progenitor cells colonize the fetal thymus

Abstract: The generation of T cells depends on the migration of hematopoietic progenitor cells to the thymus throughout life. The identity of the thymus-settling progenitor cells has been a matter of considerable debate. Here we found that thymopoiesis was initiated by a first wave of T cell lineage-restricted progenitor cells with limited capacity for population expansion but accelerated differentiation into mature T cells. They gave rise to αβ and γδ T cells that constituted Vγ3(+) dendritic epithelial T cells. Thymop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(116 citation statements)
references
References 50 publications
5
108
3
Order By: Relevance
“…Recently, it has been shown that the second wave-progenitors colonizing thymus just before birth retain robust B cell potential in addition to myeloid potential (Luc et al 2012;Ramond et al 2014). It is therefore probable that the second wave-progenitors are close to MLPs.…”
Section: Prethymic Pathway Of T Cell Developmentmentioning
confidence: 97%
“…Recently, it has been shown that the second wave-progenitors colonizing thymus just before birth retain robust B cell potential in addition to myeloid potential (Luc et al 2012;Ramond et al 2014). It is therefore probable that the second wave-progenitors are close to MLPs.…”
Section: Prethymic Pathway Of T Cell Developmentmentioning
confidence: 97%
“…*p , 0.05. cortical thymic epithelial cell differentiation can be regulated in a LTbR-dependent fashion (45). Furthermore, hematopoietic progenitors that seed the thymus comprise a relatively heterogeneous mixture of cells, including common lymphocyte progenitors and early thymic progenitors, which all express IL-7Ra (26,40). This being said, we are unable to experimentally exclude a potential role for more mature lymphoid lineages in the thymus with a history of IL-7Ra expression, although the absence of a NKT1 a subset phenotype in CD4-cre;LTb F/F , CD79a-cre;LTb F/F , and CD11c-cre;LTb F/F mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Three, potential cellular lineage(s)-expressing LTb should presumably have a nonredundant role during thymic organogenesis. Based on these criteria, we postulated that hematopoietic and/or lymphoid precursors to the T lymphocyte lineage may be viable candidates as they can be detected within the thymic anlage from E11.5 onward (39,40) and are reported to promote differentiation of thymic stromal tissue (12,41). Thus, to assess the role of hematopoietic and/or lymphoid progenitors as a cellular source for LTb during NKT1 a development , we selected a mouse line expressing cre-recombinase under the control of the IL-7Ra promoter (26).…”
Section: Lymph Node Aplasia In Germline Ltb-deficient Mice Does Not Imentioning
confidence: 99%
“…The fact that T cells can be generated from fetal HPC does not in itself prove the presence of multipotent progenitors or HSC, since it has been shown that T cells can be generated from YS precursors that arise before HSC are generated. 19,20 Selfrenewal of HSC is evaluated by their ability to reconstitute immune deficient mice. Previous studies have reported re-population by in vitro hESC-derived HPC.…”
Section: Discussionmentioning
confidence: 99%